Development of LKPD Teaching Materials Based on Community Science Technology To Improve Students’ High Level of Communication and Thinking Ability - Pihraf Risana; Tri Jalmo; Pujiati Pujiati; Dwi Yulianti; Rochmiyati Rochmiyati (research, training and philanthropy institution Natural Aceh, 2021)
This development research aims to realize the development of STM-based LKPD, to find out the effect of developing STM-based LKPD which is theoretically feasible and suitable for use by educators in classroom learning. The research method used is development research (Research and Development) by using research steps according to Borg and Gall. The population in this study were fifth grade elementary school/MI educators in Rajabasa District, Bandar Lampung City, which amounted to eight educators. The sample used in this study was a saturated sample, namely eight educators. This study uses a qualitative descriptive analysis. Data collection techniques in this study were carried out in two ways, namely observation, and questionnaires (needs analysis questionnaire). The instruments in this study consisted of: 1) needs analysis instruments, 2) materials expert validation instruments, media experts and linguists, 3) user validation instruments (educators). The results of prototype product development were validated by material experts, media experts and linguists and validated by users, namely fifth grade educators at SD/MI Rajabasa District, Bandar Lampung City, totaling eight educators to support students' communication and high-level thinking skills in the learning process in the classroom.